Spanien : Graphik - Plastik - Malerei - Sammlungskatalog - Baum, Peter; Nowak-Thaller, Elisabeth; Strohhammer, Angelika (Linz : Neue Galerie der Stadt Linz, 2001)
Arroyo, Eduardo ; Castillo, Jorge ; Chillida, Eduardo ; Gabino, Amadeo ; de Goya, Francisco ; Lobo, Baltasar ; Mira, Victor ; Miro, Joan ; Picasso, Pablo ; Hernandez Pijuan, Juan ; Plensa, Jaume ; Sapere, Horacio ; Saura, Antonio ; Tàpies, Antoni ; Vallribera, Josep ; Villalba, Darío
Duits
kunstcatalogus
Keywords: Spanje